Swedish Contextual Database for The Swedish Generations and Gender Survey and The International Generations and Gender Programme - Neyer, Gerda; Dahlberg, Johan (Stockholm University, 2018)
The Swedish Contextual Database provides a large number of longitudinal and regional macro-level indicators primarily assembled to facilitate research on the effects of contextual factors on family and fertility behavior. It can be linked to the individual-level data of the Swedish GGS as well as to data of other surveys. It can also be used for other types of research and for teaching. The comparative data will also be integrated into the international Contextual Database of the GGP. The contextual data are available open-access through the GGP webpage: www.ggp-i.org and through the webpage of Stockholm University Demography Unit www.suda.su.se

Purpose:

The Swedish contextual database (CDB) was established to accompany the Swedish Generations and Gender Survey (GGS) and to complement the contextual database of the international Generations and Gender Programme (GGP).

The Swedish Contextual Data Collection is available in xls format. In addition to that, the internationally comparative data will be integrated into the Contextual Database (CDB) of the GGP in 2018. These data can be exported in other formats, as well (e.g. CSV, XML). The indicators can also be accessed in a single file in STATA or SPSS format. The data can be matched with the Swedish GGS. International regional coding schemes are also supported, such as NUTS, OECD.

Den svenska kontextuella databasen innehåller ett stort antal longitudinella och regionala indikatorer på makronivå som insamlats i första hand för att underlätta forskning om kontextuella faktorers effekt på familjebeteende och barnafödande. Den kan kopplas till data på inidividnivå i svenska GGS liksom till data från andra surveyundersökningar. Den kan också användas till annan typ av forskning och till undervisning. Den jämförande datan kommer också integreras i den internationella kontextuella databasen hos GGP. Den kontextuella datan finns fritt tillgänglig genom GGP:s webbplats: www.ggp-i.org och genom Stockholms universitets demografiska enhets webbplats: www.suda.su.se.

Syfte:

Den svenska kontextuella databasen (CDB) skapades för att medfölja svenska Generations and Gender Survey (GGS) och för att komplettera den kontextuella databasen hos det internationella Generations and Gender Programme (GGP).

Den svenska kontextuella datasamlingen finns tillgänglig i xls-format. Dessutom kommer den internationellt jämförande datan att integreras i GGP:s kontextuella databas (CDB) under 2018. Dessa data kan också exporteras till andra format (t.ex. CSV och XML). Det är också möjligt att få tillgång till indikatorerna i en enda fil i STATA- eller SPSS-format. Datan kan matchas med svenska GGS. Internationella regionala kodningsscheman, såsom NUTS och OECD, stöds också.
Svensk kontextdatabas för den svenska Generations and Gender Survey och den internationella databasen för Generations and Gender Programme
Keywords: HOUSING; BOENDE; MIGRATION (HUMAN); MIGRATION; POLITICS; POLITIK; EMPLOYMENT; ANSTÄLLNING; ECONOMICS; EKONOMI; CULTURE; KULTUR; FISCAL POLICY; SKATTEPOLITIK; HEALTH; HÄLSA; SOCIAL WELFARE; SOCIAL VÄLFÄRD; PENSIONS; PENSION; CHILDREN; BARN; CHILD CARE; BARNOMSORG; UNEMPLOYMENT; ARBETSLÖSHET; TAXATION; BESKATTNING; EDUCATION; UTBILDNING; PARENTAL LEAVE; FÖRÄLDRALEDIGHET; LABOUR (RESOURCE); ARBETSKRAFT; DEMOGRAPHY; DEMOGRAFI; Geriatric Nursing; Äldrevård; Mortality; Dödlighet; Work; Arbete; FERTILITY (HUMAN); FRUKTSAMHET; EMPLOYMENT POLICY; SYSSELSÄTTNINGSPOLITIK; HOUSING POLICY; BOSTADSPOLITIK; Longevity; Livslängd; Pensions; Pensioner; Life Tables; Dödlighetstabeller; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Economic policy, public expenditure and revenue; Ekonomisk politik, offentliga utgifter och intäkter; Compulsory and pre-school education; Obligatorisk utbildning och förskoleutbildning; Higher and further education; Gymnasial och högre utbildning; Health care services and policies; Hälso- och sjukvårdstjänster och -politik; Employment; Sysselsättning; Unemployment; Arbetslöshet; Retirement; Pension; Elections; Val; Family life and marriage; Familjeliv och äktenskap; Elderly; Äldre; Children; Barn; Social welfare policy; Välfärdspolitik; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social conditions and indicators; Sociala förhållanden och indikatorer; Social change; Social förändring; Social Sciences; Samhällsvetenskap